Stress effects on gastrointestinal transit in the rat. Issue 4 (April 1989) - Enck, P; Merlin, V; Erckenbrecht, J F; Wienbeck, M
Abstract : Previous investigations of stress effects on gastric emptying, orocaecal, and colonic transit in rats have produced conflicting results. Here one type of stressor, a 'passive avoidance' situation, was used to investigate its effects on gastric emptying, orocaecal and colonic transit. After the rats had been trained to eat a standard amount of semisolid food, gastric emptying was determined (n = 12) by the food remaining in the stomach after various periods of rest, or stress exposure. Orocaecal transit (n = 14) was determined by breath hydrogen measurements after the food had been labelled with 1 g lactose. Colonic transit (n = 18) was measured as the arrival time of coloured faeces after infusion of a carmine red solution into the caecum through a chronically implanted catheter. The stressor had differential effects on transit through the stomach, small bowel and colon: gastric emptying was delayed (p less than 0.05) after stress (t1/2 = 2.66 h after stress, 1.97 h at rest). Orocaecal transit was accelerated (p less than 0.05) after stress; transit time decreased from 124.3 min at rest to 86.2 min after stress. Colonic transit was accelerated (p less than 0.01) under stress, from 15.5 h to 1.29 h. It is concluded that gastrointestinal transit in different parts of the gastrointestinal tract is differently affected by central nervous stimuli.